SAT0220 Radiographic Progression in Modern RA Trials is Still a Robust Outcome: Results of Comprehensive Sensitivity Analysis in Two Phase 3 Trials with Tofacitinib. (9th June 2015) - van der Heijde, D.; Connell, C.; Bradley, J.; Gruben, D.; Strengholt, S.; Landewé, R.B.
Abstract : Background: Tofacitinib is an oral Janus kinase inhibitor for the treatment of RA. In Phase 3 ORAL Scan (NCT00847613 ; MTX-inadequate responders) and ORAL Start (NCT01039688 ; MTX-naïve) 24-month studies, progression in radiographic scores of the protocol-specified primary analysis at the 12-month interim was measured by mean change from baseline (BL) in van der Heijde modified Sharp scores (mTSS) at Month 6. This co-primary endpoint was analysed using Analysis of Covariance (ANCOVA). In ORAL Scan, tofacitinib 10 mg but not 5 mg twice daily (BID) demonstrated statistically significant inhibition of progression in mTSS vs placebo (PBO). In ORAL Start, tofacitinib 5 and 10 mg BID doses showed statistically significant inhibition of progression in mTSS vs MTX. Mean change from BL in mTSS at Month 6 was 0.47 with PBO in ORAL Scan and 0.84 with MTX 20 mg/week in ORAL Start. Objectives: To better understand the degree to which radiographic progression was inhibited by tofacitinib in two different patient populations. The goals of these analyses were to demonstrate: 1) the magnitude of tofacitinib efficacy in the presence of predictors of higher risk of structural progression, and 2) whether the results were driven by outliers. The latter was approached by use of a trimmed analysis, whereby extreme values are systematically removed. Methods: A literature review was performed for factors predicting higher risk of structural progression. BL data were used to subset the patients by these high-risk factors, tailored to the tofacitinib program, regardless of treatment group assignment. ANCOVA was then applied to each high-risk subset. For trimmed analyses, data were trimmed in 1% increments up to 10% (2% trimming deletes observations >1st and <99th percentile) and ANCOVA was applied to each trimmed data set. Results: High-risk factors for radiographic progression within the tofacitinib program included: anti-CCP+; BL DAS28-4(ESR) >5.1; CRP+ (>7 mg/L); both seropositive (RF+ or anti-CCP+) and BL erosion score ≥3; and, >median BL mTSS. For mTSS, high-risk subsets generally showed greater differentiation, although the degree of differentiation varied by BL risk (Figure ). With regard to trimmed analyses, in ORAL Scan, statistical significance (p≤0.05; not corrected for multiple comparisons) was achieved for both tofacitinib doses at 1% trimming, and the significance was maintained with further trimming, with mean values stable at 3%. The trimmed analyses in ORAL Start showed that statistical significance in both doses was maintained, and the upper limit of the confidence intervals remained stable for tofacitinib 5 and 10 mg BID. Conclusions: In ORAL Scan and ORAL Start, both tofacitinib 5 and 10 mg BID demonstrated inhibition of structural damage progression vs comparator in high-risk patients, and the trimmed analyses demonstrate that significant inhibition of structural damage was not driven by outliers. These results show that the degree of inhibition of radiographic progression is consistent across the two patient populations. Acknowledgements: Study sponsored by Pfizer Inc. Editorial support was provided, under the guidance of the authors, by A Smith, PhD, of CMC, and funded by Pfizer Inc. Disclosure of Interest: D. Van der Heijde Consultant for: AbbVie, Amgen, AstraZeneca, Augurex, BMS, Boehringer Ingelheim, Celgene, Centocor, Chugai, Covagen, Daiichi, Eli-Lilly, Galapagos, GSK, Janssen Biologics, Merck, Novartis, Novo-Nordisk, Otsuka, Pfizer Inc, Roche, Sanofi-Aventis, UCB, Vertex, Employee of: Imaging Rheumatology, C. Connell Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Bradley Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Gruben Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Strengholt Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, R. Landewé Grant/research support from: Pfizer Inc, Abbott, Janssen, Merck, Consultant for: Abbott, Amgen, Astra, Bristol-Myers Squibb, Centocor, GlaxoSmithKline, Janssen, Pfizer Inc, UCB, Vertex